Subglottic Schwannoma: A rare cause of dyspnea - Joana Gonçalves; Jorge Miguéis; Ant´ónio Jorge Ferreira; Nuno Silva; Clara Silva; Ana Margarida Amorim; Luís Silva (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
A young woman with persistent cough, dysphonia, and progressive dyspnea for 6 months was referred to the pneumologist. Her pulmonary function tests revealed airway obstruction with increased airway resistance and hyperinflation, but with no response to bronchodilators. High resolution CT scan showed a right-sided, lobulated, infraglottic lesion, reducing by 50 to 75% the airway lumen. Video-bronchoscopy confirmed the presence of two vascularized infraglottic lesions and biopsy was performed. Complete surgical excision was achieved via a combined technique (endolaryngeal and medial cervicotomy approaches). The histopathological diagnosis was laryngeal schwannoma. At 6 months follow-up, cough and hoarseness had resolved, and indirect laryngoscopy showed normal vocal cord mobility without tumor recurrence.